2004
DOI: 10.1159/000076943
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tracheal Responsiveness to Beta-Adrenergic Agonist and Antagonist in Ovalbumin-Sensitized Guinea Pigs

Abstract: Despite the controversy of bronchial responsiveness to β2-agonist drugs in asthma, in a previous study we have shown increased responsiveness of asthmatic tracheobronchial tree to isoprenaline. Therefore, in the present study, tracheal responsiveness to isoprenaline and also β-adrenergic receptor blockade were studied in sensitized guinea pigs. An experimental model of asthma was induced in guinea pigs by sensitization of animals with injection and inhalation of ovalbumin (OA). The responses of trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
4
5
0
Order By: Relevance
“…The histological findings in AECS showed increased interalveolar septum and lymphatic tissue, destruction of alveolar walls and intra‐alveolar bleeding as was to that observed in previous studies 5,25 , 26 . The increased tracheal response to isoprenaline in AECS + sensitized confirmed the induction of experimental asthma and the tracheal responsiveness to a β‐agonist drug was similar to our previous studies 15–18 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The histological findings in AECS showed increased interalveolar septum and lymphatic tissue, destruction of alveolar walls and intra‐alveolar bleeding as was to that observed in previous studies 5,25 , 26 . The increased tracheal response to isoprenaline in AECS + sensitized confirmed the induction of experimental asthma and the tracheal responsiveness to a β‐agonist drug was similar to our previous studies 15–18 …”
Section: Discussionsupporting
confidence: 89%
“…The increased propranolol blockade in tracheal chains of AECS and AECS + sensitized guinea pigs, as well as the increased chlorpheniramine, atropine, and propranolol blockade in our previous in vivo studies in asthmatic patients 15,42 , 44 and enhanced atropine, chlorpheniramine and propranolol blockade in tracheal chains of sensitized animal studies, 16,27 , 28 could be due to higher concentration of antagonists at the receptor sites achieved by an increased epithelial and tissue permeability leading to an increase in [I]. Destruction of lung parenchyma has been documented in AECS 21 and thus, increased tissue permeability and better accessibility of ligands to the receptor sites is possible.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[12] This hypothesis was then tested with another β-agonist (salbutamol) in asthmatic patients and also in smokers. [13,14] This phenomenon was also demonstrated in tracheal chains of sensitized and COPD animals [30,31] as well as epithelial denuded trachea. [32] In most of the above-mentioned studies a close correlation was found between airway responsiveness to methacholine and β-agonist.…”
Section: Discussionmentioning
confidence: 95%